CONSTITUTIONAL DISOBEDIENCE PUTUSAN MAHKAMAH KONSTITUSI: KAJIAN TERHADAP PERPPU CIPTA KERJA: Constitutional Disobedience of Constitutional Court Decisions: A Study of Job Creation Government Regulation in Lieu of Law - Aprilian Sumodiningrat (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Government Regulation in Lieu of Law Number 2 Year 2022, concerning on Job Creation, was issued based on several considerations, such as the urgency of geopolitical crisis caused by Russian-Ukraine war, the worsening of world economic chain, the inflation threat, the stagflation, and also the need for investor certainty. The issue definitely does not reflect the meaningful participation in acts formation as stated by Constitutional Court decision No. 9/PUU-XVIII/2020. The study aims to examine the Constitutional Disobedience for Job Creation Government Regulation in Lieu of Law. The research findings are as follows; the first, the condition of compelling emergency within was not met, so that it could be rescinded by the Constitutional Court; the second, its issue could be categorized as defiance of that Constitutional Court decision previously stated, since it did not match what it was instructed, yet not based on objective situation. Keywords: Perppu; Constitutional Dissobedience, President. Perppu nomor 2 tahun 2022 tentang Cipta Kerja dikeluarkan dengan beberapa pertimbangan, seperti adanya kegentingan memaksa berupa krisis geopolitik yang disebabkan oleh peperangan Rusia Ukraina, rantai ekonomi dunia yang semakin memburuk, ancaman inflasi, stagflasi, hingga perlunya kepastian investor. Penerbitan Perppu tersebut, tentu tidak mencerminkan adanya meaningful participation dalam pembentukan undang-undang sebagaimana putusan MK No. 9/PUU-XVIII/2020. Penelitian ini bertujuan untuk mengkaji mengenai Constitutional Disobedience dalam penerbitan Perppu Cipta Kerja. Hasil penelitian ini menunjukkan, pertama, syarat